1998
DOI: 10.1063/1.366951
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties enhancement of α-Fe/Nd2Fe14B-type nanocomposites by Co substitution

Abstract: The phase evolution and magnetic properties of melt-spun Nd9.5(Fe1−xCox)85.5B5 (x=0, 0.05, 0.1, and 0.15) nanocomposites have been investigated. It was found that Co substitution for Fe, i.e., x=0.05–0.15, improves the Curie temperature (Tc), remanence (Br), and maximum energy product (BH)max of the materials obtained. Co substitution for Fe was found to promote grain coarsening, after thermal processing, in materials with a high Co concentration. Wohlfarth remanence analysis suggests that dilute-Co substituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 13 publications
2
21
1
Order By: Relevance
“…Correspondingly, it is found that the remanence of the ribbons displays a similar tendency with the increase of x. A similar phenomenon was also observed in the Nd 2 Fe 14 B/␣-Fe-type nanocomposites [6]. …”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Correspondingly, it is found that the remanence of the ribbons displays a similar tendency with the increase of x. A similar phenomenon was also observed in the Nd 2 Fe 14 B/␣-Fe-type nanocomposites [6]. …”
Section: Resultssupporting
confidence: 64%
“…A heat treatment applied to selected ribbons at 650-750 • C for 10 min cause them to crystallize, improving their magnetic properties. Characterization techniques for the ribbons were reported elsewhere [6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is emphasized here that Sm decreases the magnetocrystalline anisotropy field and saturation magnetization, so the coercivity and remanence of Nd 7.8 Sm 0.2 Fe 86 B 6 ribbons are lower than that of pure Nd 8 Fe 86 B 6 ribbons. This could be improved by substitution of Co for Fe and substitution of Dy for Nd [16,17].…”
Section: Resultsmentioning
confidence: 97%
“…A disadvantage of the nanocomposite alloys is the decrease in i H c accompanying the M r enhancement, which adversely affects (BH) max , in spite of the continuing increase in M r . Many attempts have been made to improve i H c and (BH) max of the nanocomposites further by elemental substitution [7][8][9][10][11]. One such attempt is partial replacement of Nd by Pr or Dy rare earth elements.…”
Section: Introductionmentioning
confidence: 99%